Investigations into the metal species of the homogeneous iron(iii) catalyzed Michael addition reactions - Bauer, Matthias; Kauf, Thomas; Christoffers, Jens; Bertagnolli, Helmut (Physical Chemistry Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Confined phonons in glasses - A study by nuclear inelastic absorption and Raman scattering - Asthalter, T.; Bauer, Matthias; van Bürck, U.; Sergueev, I.; Franz, H.; Chumakov, A.I. (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Structural Investigation of High-Valent Manganese–Salen Complexes by UV/Vis, Raman, XANES, and EXAFS Spectroscopy - Feth, Martin P.; Bolm, Carsten; Hildebrand, Jens P.; Köhler, Manuela; Beckmann, Oliver; Bauer, Matthias; Ramamonjisoa, Rivo; Bertagnolli, Helmut (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Phonons in Confinement and the Boson Peak Using Nuclear Inelastic Absorption - Asthalter, T.; Bauer, Matthias; van Buerck, U.; Sergueev, I.; Franz, H.; Chumakov, A. I. (Hyperfine Interactions)
We have applied nuclear inelastic absorption (NIA) to the molecular glass former dibutylphthalate/ferrocene, both in bulk and in nanoporous matrices having pore sizes of 50 and 25 A, respectively. The quantity g(E)/E2, where g(E) is the vibrational phonon density of states (VDOS) of the resonant nuclei, exhibits a pronounced maximum at low energies. Confinement in pores leads to a suppression of the VDOS below 1.5 meV, independent of the pore size. Also in the scaled heat capacity C(T)/T3, we observe a decrease of the peak maximum for low temperatures. Our observations are discussed in the light of experimental and theoretical results on nanocrystals and a recent theoretical model for the boson peak.